1985
DOI: 10.3109/00016348509155123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Alphafetoprotein (Afp) Levels at Term

Abstract: Serum alpha-fetoprotein (AFP) was measured in maternal, cord arterial and venous blood. Samples were collected at the time of vaginal delivery from 105 women at 36-42 weeks' gestation. There was a significant correlation between maternal, cord arterial and venous AFP. Umbilical cord arterial and venous AFP levels were considerably higher in male infants than in females. Umbilical AFP levels declined with lengthening gestation and increasing birthweight for both male and female infants and a similar pattern was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…The present study confirms and extends previous observations that maternal AFP se rum levels are related to fetal sex [25][26][27][28][29]. If fetal sex is disregarded when setting limits for normal maternal serum AFP levels in the screening procedure, it is to be expected that more women carrying male rather than fe male fetuses will be ranked as 'risk' patients.…”
Section: Discussionsupporting
confidence: 79%
“…The present study confirms and extends previous observations that maternal AFP se rum levels are related to fetal sex [25][26][27][28][29]. If fetal sex is disregarded when setting limits for normal maternal serum AFP levels in the screening procedure, it is to be expected that more women carrying male rather than fe male fetuses will be ranked as 'risk' patients.…”
Section: Discussionsupporting
confidence: 79%
“…Since higher testosterone levels have been measured in amniotic fluid from pregnancies of male fetuses [10], one possibility would be to assess the net effect of sex hormones on AFP production by measuring the AFP levels in the fetal blood. In fact, umbilical cord arterial and venous AFP levels are considerably higher in male than in female infants [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis can hardly explain two facts: (1) The inverse correlation between fetal (umbilical cord) AFP levels and birth weight [10][11][12] ; (2) MSAFP increases several weeks before both IUGR and any kind of placental lesions are manifest even though it has been speculated that these placental pathological changes can have their origin in the second trimester, although they are not evident until later in pregnancy [13] . In addition, in situations in which there is a clear placental abnormality that may lead to MSAFP elevations such as placental separation, stratified analyses have demonstrated that elevations of MSAFP and early gestation bleeding are independent predictors of low birth weight infants [14] .…”
Section: Discussionmentioning
confidence: 99%